Portrait of George Trapp - Beneker, Gerrit A. (Gerrit Albertus) (1930)
Standing portrait of George Trapp, a blue-collar worker, looking left; dressed in work clothes including a cap, white shirt, vest, and smock; holding the neck of a green glass carboy in left hand; to left, crates used to transport carboys, labeled VITRIOL; factory interior and tools of the trade visible in background. Gilded frame with label: "GEORGE TRAPP / OIL OF VITRIOL DEPT. / EMPLOYED 1881-1932". Oil of vitriol is a historic name for sulfuric acid. Sulfuric acid is used in industrial contexts to manufacture chemicals, fertilizers, and explosives. Artist Gerrit A. Beneker (1882-1934) was an American painter and illustrator, particularly known for his paintings of American industry in the 1920s. Otto Haas commissioned Beneker to paint a series of pictures showing Bridesburg employees.
Keywords: Employees; Blue collar workers; Pennsylvania--Philadelphia--Bridesburg; Rohm and Haas Company; Sulfuric acid